Le emozioni tra arte e psicologia. Alcune osservazioni su Wittgenstein e l’estetica - Valeri, Elena (Rivista Italiana di Filosofia del Linguaggio, 2020)
The radical antipsychologism of Wittgenstein and the lack of relevance which he ascribes to causal (empirical-physiological) links between works of art and psychological reactions seem to allow no room for a positive consideration of emotions, and to disable any attempt to assign aesthetic value to the emotional element. Presenting and discussing some of Wittgenstein’s insights on the aesthetic experience (§§ 1-2) and on the concept of emotion (§ 3), I will argue that this is actually not the case. Rather, for a Wittgensteinian (in inspiration) aesthetics or philosophy of art emotions are certainly important. In particular, my suggestion is that for Wittgenstein emotions are definitely part of our way of speaking about art, and the relationship between emotions and (works of) art which has some validity in aesthetics is the one of inherence or immanence: we use emotions to describe (works of) art in words and by doing so, we also define the quality of emotions, making them understandable to us through art.